THE PHENOMENON OF ‘TRAVELOKA XPERIENCE’ FROM THE PERSPECTIVES OF ENTERTAINMENT MEDIA ENTHUSIASTS IN SURABAYA - Iin Rachmawati (Universitas Terbuka, 2021)
Recently, it can be seen that there are numerous ways when it comes to go around the world or when it comes to search for entertainment. Internet has provided everything we need just for a few clicks. This article will discuss about the new phenomenon in the entertainment industry called ‘Traveloka Xperience’. By using this feature, the users can easily search for everything related to entertainment facility they want in just one application such as traveling, eating, watching movies, going to spa, and many others. Qualitative descriptive approach will be used to help finding how the interaction built between the users and the text, as well as about the influence of Traveloka Xperience towards the fast development of entertainment industry business and how their users utilize this feature to fulfill their needs in searching for alternative entertainment facility. The result shows that there are still various entertainment business chances, especially some sort of start-up business. The users of Traveloka Xperience have also considered that these kinds of tertiary experiences are becoming something they need the most.